The N‐end rule adaptor protein ClpS from Plasmodium falciparum exhibits broad substrate specificity. Issue 19 (23rd September 2016) - Tan, Ju Lin; Ward, Linda; Truscott, Kaye N.; Dougan, David A.
Abstract : The N‐end rule is a conserved protein degradation pathway that relates the metabolic stability of a protein to the identity of its N‐terminal residue. Proteins bearing a destabilising N‐terminal residue (N‐degron) are recognised by specialised components of the pathway (N‐recognins) and degraded by cellular proteases. In bacteria, the N‐recognin ClpS is responsible for the specific recognition of proteins bearing an N‐terminal destabilising residue such as leucine, phenylalanine, tyrosine or tryptophan. In this study, we show that the putative apicoplast N‐recognin from Plasmodium falciparum ( Pf ClpS), in contrast to its bacterial homologues, exhibits an expanded substrate specificity that includes recognition of the branched chain amino acid isoleucine. Abstract :